2018
DOI: 10.1177/1947603518783495
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Carprofen Is Enhanced by Avocado/Soybean Unsaponifiables, Glucosamine and Chondroitin Sulfate Combination in Chondrocyte Microcarrier Spinner Culture

Abstract: Objective Osteoarthritis is a painful, chronic joint disease affecting man and animals with no known curative therapies. Palliative nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used but they cause adverse side effects prompting the search for safer alternatives. To address this need, we evaluated the anti-inflammatory activity of avocado/soybean unsaponifiables (ASU), glucosamine (GLU), and chondroitin sulfate (CS) with or without the NSAID carprofen. Design Canine chondrocytes were propagated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 63 publications
(210 reference statements)
0
4
0
Order By: Relevance
“…Likewise, Grzanna et al (2010), using monocyte/macrophage cell models, determined the inhibitory effects of ASU extract (8.3 µg/mL) in combination with chondroitin sulfate (CS) (20 µg/mL) on both the synthesis and expression of pro-inflammatory stimulators and mediators, such as cytokine expression and PGE-2 production [88]. An addition, Grzanna et al (2018) carried out another study where ASU extract was used with glucosamine (GLU), CS and with or without the presence of carprofen, a nonsteroidal anti-inflammatory drug (NSAID) [89]. The aim of this study was to assess the anti-inflammatory activity using a composite mixture of ASU extract (8.3 µg/mL), GLU (11 µg/mL), CS (20 µg/mL) and/or the NSAID carprofen (40 ng/mL).…”
Section: In Vitro and In Vivo Studies Of Asu In Osteoarticular Disordersmentioning
confidence: 99%
“…Likewise, Grzanna et al (2010), using monocyte/macrophage cell models, determined the inhibitory effects of ASU extract (8.3 µg/mL) in combination with chondroitin sulfate (CS) (20 µg/mL) on both the synthesis and expression of pro-inflammatory stimulators and mediators, such as cytokine expression and PGE-2 production [88]. An addition, Grzanna et al (2018) carried out another study where ASU extract was used with glucosamine (GLU), CS and with or without the presence of carprofen, a nonsteroidal anti-inflammatory drug (NSAID) [89]. The aim of this study was to assess the anti-inflammatory activity using a composite mixture of ASU extract (8.3 µg/mL), GLU (11 µg/mL), CS (20 µg/mL) and/or the NSAID carprofen (40 ng/mL).…”
Section: In Vitro and In Vivo Studies Of Asu In Osteoarticular Disordersmentioning
confidence: 99%
“…DA, 5-HT is a peripheral pain medium, which can stimulate sensory peripheral nerves to make the body feel pain [25]. PGE2 can be produced in large quantities in the early stage of inflammation, reduces the pain threshold in the local area of inflammation, and activates the EP receptors on the peripheral sensory nerve endings to enhance the pain sensation [26]. is study found that warm acupuncture combined with meloxicam and comprehensive nursing could significantly reduce the content of pain mediator (PGE2, SP, DA, and 5-HT) in patients with KOA, indicating that meloxicam combined with warm acupuncture has a good analgesic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, carprofen was used for the treatment of gastrointestinal pain and nausea. Later, it is banned due to its toxicity [ 88 , 89 ].…”
Section: Pyrrole and Pyrrolidine Drug Candidatesmentioning
confidence: 99%
“…Fakhar et al [154] report based on the structure-based pharmacophore modeling, virtual screening workflow, ADMET, and molecular dynamics simulations revealed that compound ABBV-744 (87) has a strong affinity (ΔGbind − 45.43 kcal/mol) to the main protease. Further, this study also considered the other two compounds (88,89) as potential inhibitors of SARS-CoV-2. In the year 2021, by the experimental evidence, Varghese et al [155] have proposed a combination of obatoclax and berberine as possible antiviral drugs for SARS-CoV-2 infection (Fig.…”
Section: Antiviral Agentsmentioning
confidence: 99%